A Comparative study of Ibu by Ahmad Jaafar and its arrangement by Iskandar Ismail / Mohd Rizdzuwan Md Jusoh - Md Jusoh, Mohd Rizdzuwan (2016)
Generally, this study has been conducted to make a comparative on harmony and music arrangement of Ahmad Jaafar's "Ibu". Therefore, this study looks forward to a sympathetic of tips and secret that makes Ahmad Jaafar become successful in his career life of music with an unique idea in his composition and arrangement. This research also has been analysed on the harmonic structure, and the music arrangement between two different versions of "Ibu". In conclusion, the study has discovered that both composer and arranger clearly like to uses diatonic harmony with some usage of secondary and subdominant in his composition and arrangement. Iskandar Ismail also uses the inversion of the chords to create a smooth and linear bass motion with structured and well-organized chords.